ANTIBODY TITER OF LOCAL DOGS SIX MONTHS ON RABIES VACCINATION - Sudarmayasa, I Nengah; Suardana, Ida Bagus Kade; Suartha, I Nyoman (Buletin Veteriner Udayana, 2020)
Rabies is a zoonotic disease that can be transmitted from animals to humans. Most cases of rabies (98%) were caused by the bite of dogs infected with rabies, while the rest by the cats. This study aims to determine the antibody titer six months y.o local dog after the rabies vaccination using vaccines rabisin. This research was conducted in three stages, namely: taking blood samples in the villages of Buduk and Sading, serum sampling and serum testing using an enzyme linked immunosorbent assay (ELISA) test using 19 samples of local dogs with random blood sampling. The results showed that from 19 samples tested 17 samples (89%) had protective antibody titers (seropositive) and two samples (11%) did not have protective (seronegative) antibody titers. Seropositive was the value of Optical Density (OD) above 0, 5 IU, while seronegative is the value of Optical Density (OD) below 0.5 IU.